2017
DOI: 10.3748/wjg.v23.i34.6201
|View full text |Cite
|
Sign up to set email alerts
|

Evidences supporting the vascular etiology of post-double balloon enteroscopy pancreatitis: Study in porcine model

Abstract: Double balloon enteroscopy (DBE) is an endoscopic technique broadly used to diagnose and treat small bowel diseases. Among the associated complications of the oral DBE, post-procedure pancreatitis has taken the most attention due to its gravity and the thought that it might be associated to the technique itself and anatomical features of the pancreas. However, as the etiology has not been clarified yet, this paper aims to review the published literature and adds new results from a porcine animal model. Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…No differences were observed between single and double balloon endoscopies in a randomised multicentre trial including 130 patients 79 as well as in two recent meta‐analyses 80,81 . Aetiology has not been defined yet, but the most likely mechanism seems to be related to vascular distress causing a hypoxic state, as supported by the experimental evidence of hypoxic areas and necrotic zones in the pancreatic tissue of pigs 82 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…No differences were observed between single and double balloon endoscopies in a randomised multicentre trial including 130 patients 79 as well as in two recent meta‐analyses 80,81 . Aetiology has not been defined yet, but the most likely mechanism seems to be related to vascular distress causing a hypoxic state, as supported by the experimental evidence of hypoxic areas and necrotic zones in the pancreatic tissue of pigs 82 …”
Section: Resultsmentioning
confidence: 95%
“…Several studies retrieved in the present systematic review reported other possible causes of AP, represented by duodenal and/or papillary lesions, procedural accidents due to either endoscopic balloons, or endoscopic retrograde cholangiopancreatography (ERCP), and primary sclerosing cholangitis (PSC) 69–89 …”
Section: Resultsmentioning
confidence: 99%
“…However, the pancreatic body and tail were the main parts affected by pancreatitis, and prolonged me-chanical torsion of the pancreatic body caused by repeated stretching was considered the most appropriate suggestion [17,18]. Based on an experiment using a porcine animal model, Latorre et al suggested that vascular distress is the most likely cause of pancreatitis after DBE [19]. The shared and primary belief noted in the literature is that the increased levels of pancreatic serum enzymes are associated with the technique itself [20 -22].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of one or more pancreatic serum marker (e.g., hyperlipasemia) is very common after an anterograde DBE procedure of long duration, and acute pancreatitis may occur in patients who had abdominal pain when they underwent anterograde DBE. 35 Normally, the amylase level would be checked after a >2-hour procedure using the anterograde approach in our center.…”
Section: Discussionmentioning
confidence: 99%